Pengaruh Perceived Ease of use Dan Service Quality Terhadap Customers Satisfaction Yang Dimediasi Trust Pada Pengguna Grab Di Kota Bandung - Aprilia, Sintha; Tania Adialita (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
His study aims to identify the influence of perceived ease of use and service quality on customer satisfaction, with trust as an intervening variable. Exploring the decline in users of the Grab app in Indonesia from 2020 to 2023, even though Grab is the online transport market leader in Southeast Asia. With more than 185,000 drivers and 10 million passengers in ASEAN, the Grab online transportation service Brand Index has experienced a significant drop of 8.2%, while its competitor continues to rise. The study applied a quantitative method to the collection of primary data through the use of online questionnaires distributed to the Z generation aged 17–28, with a total sample of 160 respondents through purposive sampling. Data analysis uses SPSS 23, and data analysis methods involve validity and reliability tests, classical assumption tests, hypothesis tests as well as sobel test. The results showed that perceived ease of use had no significant impact on trust, while service quality had a significant influence on trust. Perceived ease of use did not have a significant effect on customer satisfaction.